Enhancing Recount Text Writing Skills Through Discussion Board Utilization - Syafii, Muhammad Lukman; Sugianto, Alip; Cendriono, Nanang; Sutanto, Sutanto (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
The aim of this study was to improve the learners' proficiency in using the discussion board to create a recount text. Presently, internet education has garnered substantial acclaim and is widely employed worldwide. The objective of the study was to enhance the writing aptitude of eighth-grade pupils in the genre of recount texts through the utilization of discussion boards. The study was conducted using a collaborative classroom action research methodology. The data sources included field notes, questionnaires, observation checklists, and the students' results, which were a recount text. The findings demonstrated that the employment of a discussion board can improve the quality of recount writing. As per the initial success criterion, a minimum score of 65 was required for 70% of the pupils. 81.48% (22 out of 27) of the students who turned in writing samples in the first round met the initial success criterion by scoring 65 or higher. Approximately 82.30% of the pupils actively participated in Education and acquisition of knowledge. The survey findings showed that following the implementation of the discussion board, a meaningful majority of students (84.70%) voiced positive reactions.